Phosphoramidite building blocks with protected nitroxides for the synthesis of spin-labeled DNA and RNA - Weinrich, Timo; Jaumann, Eva A.; Scheffer, Ute M.; Prisner, Thomas F.; Göbel, Michael W. (Beilstein Journal of Organic Chemistry, 2018)
TEMPO spin labels protected with 2-nitrobenzyloxymethyl groups were attached to the amino residues of three different nucleosides: deoxycytidine, deoxyadenosine, and adenosine. The corresponding phosphoramidites could be incorporated by unmodified standard procedures into four different self-complementary DNA and two RNA oligonucleotides. After photochemical removal of the protective group, elimination of formic aldehyde and spontaneous air oxidation, the nitroxide radicals were regenerated in high yield. The resulting spin-labeled palindromic duplexes could be directly investigated by PELDOR spectroscopy without further purification steps. Spin–spin distances measured by PELDOR correspond well to the values obtained from molecular models.
Keywords: EPR; oligonucleotide; PELDOR; photolabile protection; TEMPO